MANAJEMEN PRODUKSI KONTEN ‘SKETSAMU’ DI YOUTUBE MUHAMMADIYAH CHANNEL - Rhafidilla Vebrynda (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Muhammadiyah is one of the largest Islamic organizations in the world. In the midst of the development of social media, YouTube has become one of the choices for Muhammadiyah's da’wah media. SketsaMu is one of the da'wah video rubrics on the Muhammadiyah YouTube Channel (Muhammadiyah's official YouTube). This research focuses on the management of YouTube content production in the SketsaMu rubric. This study uses the concept of Eli M Noam about the key factors for the success of media production, there are, risk reduction, product development and organizational structure. This research use case study with qualitative research method. Data collection uses interviews, observations and documentation. This study found that the first concept of reduction is by adjusting the target audience and distributing the platform. The second concept is in the product development process, namely by writing, editing, revising and developing programs. The last factor of the organization is still not implemented optimally, all production processes to distribution are still carried out by one team, so the workload becomes a lot.